derive second equation of motion
Answers
Answered by
10
→Distance = Average velocity × time
→Average velocity = (u+v)/2
Then s=(u+v)/2×t
According to first equation if motion,
v = u + at
substituting the value of v in above equation
s = (u+u+at)/2 x t
→s = (2u+at)/2 × t
→s = (2ut+at²)/2
→s = 2ut/2 + at²/2
→s=ut+1/2at²
Hence derived.
Answered by
1
→Distance = Average velocity × time
→Average velocity = (u+v)/2
Then s=(u+v)/2×t
According to first equation if motion,
v = u + at
substituting the value of v in above equation
s = (u+u+at)/2 x t
→s = (2u+at)/2 × t
→s = (2ut+at²)/2
→s = 2ut/2 + at²/2
→s=ut+1/2at²
Hence derived.
Similar questions
Social Sciences,
4 months ago
Biology,
4 months ago
English,
4 months ago
Computer Science,
9 months ago
English,
9 months ago
Physics,
1 year ago
Math,
1 year ago
Math,
1 year ago